Domain-specific physical activity among indigenous overweight and obese communities in Sarawak - Cheah, Whye Lian; Helmy, Hazmi; Ching, Thon Chang; Wan Abdul Manan, Wan Muda (BJHPA, 2016)
Physical activity is important to maintain health and to prevent non-communicable diseases. Material/Methods We evaluated physical activity in four domains (leisure time, occupational, domestic and transportation ones) and its sociodemographic correlates in 351 adult overweight and obese indigenous people in Sarawak, Malaysia. Physical activity was assessed using the Malay version of the International Physical Activity Questionnaire (IPAQ) long form. The data were analysed using SPSS version 20. Results More than 40% of the respondents (43.5%) were obese. The overall median total MET-minutes were 6180.0 (IQR = 10229.0). A total of 53% of the respondents were moderately active with the majority of them being female (55.6%). The overall median total MET-minutes were low for leisure and transportation domains. Females were more active in the domestic domain, while males in the work and leisure-time domains of physical activity. Younger respondents (< 30 years) had the lowest level of physical activity. There is a significant positive relationship of gender with work, domestic and leisure-time domains of physical activity, and of occupation with work and leisure-time domains as well as all domains of physical activity. Conclusions Studies on physical activity among overweight and obese adults should examine all domains in order to understand its relationship and weight problem.